New attempt in tuberculosis treatment: autologous cytokine-induced killer after chemotherapy treatment failure in a case of multi-drug resistant tuberculosis(MTB) - Xu, Junchi; Chen, XinNian; Ye, ZhiJian; Wu, Meiying; Shi, Cuilin; Tang, Peijun; Chen, Hui; Zhu, Xiaoyan; Song, Huafeng; Xu, Ping (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
A 32-year-old woman was diagnosed as pulmonary tuberculosis 15 years ago and recurred several times due to long-term nonstandard treatment. Drug sensitivity test indicated that multidrug-resistant tuberculosis had emerged and we determined relevant therapeutic schedule according to this result. However, it didn’t show any amelioration of the disease after 3-month chemotherapy. We formulated 3-course CIK immunotherapy based on patient’s condition. After 3 courses of immunotherapy, we found obvious amelioration of the patient’s condition. And there was no recurrence during the follow-up in the past 3 years. Therefore, we considered that the CIK immunotherapy is an effective method for tuberculosis treatment and recurrence prevention.